Essays on spatial economics and international trade - HU, Naiyuan (Institutional Knowledge at Singapore Management University, 2024)
This dissertation consists of three papers on spatial economics and international trade. The first paper focuses on spatial inequalities. Educational resources are distributed unevenly and contribute to spatial inequality. A dynamic spatial model with life-cycle elements studies the impacts of location-specific educational resources. Individuals determine where to attend college, weighing distance, expected value of education, and available resources. Locations with more colleges attract more students. As mobility costs increase with age, many graduates stay in the city where they studied, affecting skill composition. Applied to China, it finds that the 2005- 2015 college expansion had minimal welfare impacts and suggests better resource distribution could reduce inequality. The second paper considers the U.S.–China trade war. U.S. President Joe Biden has maintained Trump tariffs on Chinese imports, despite the promise to remove them before the 2020 presidential election. The hypothesis that these tariffs can serve as leverage in future tariff negotiations with China is investigated using a quantitative model that incorporates U.S. regions and international trade linkages. After estimating the bargaining power of the U.S. and China, their cooperative tariffs starting from the 2017 baseline and 2019 trade-war equilibrium are computed separately. Simulation results show that, regardless of the relative bargaining power of the U.S., the trade war always improves U.S. welfare in the post-negotiation cooperative equilibrium. With an estimated Nash bargaining weight between 0.47 and 0.70, the trade war with China yields a post-negotiation welfare improvement of 0.04The third paper focuses on trade policy and sanctions against Russia. It examines the most cost-efficient ways to impose sanctions. A quantitative model of international trade is employed. It finds that for countries with low willingness to pay, a uniform 20% tariff on all Russian products is optimal. For countries willing to pay at least $0.70 for each $1 drop in Russian welfare, an embargo on Russia’s mining and energy products, with tariffs above 50% on other products, is most efficient. If countries target politically relevant sectors, an embargo on Russia’s mining and energy sector remains cost-efficient, even with low willingness to pay for sanctions.